Recent Advances in MnFe2O4/Activated Carbon Composites for Environmental and Energy Applications: A Comprehensive Review on Synthesis, Characterization, and Performance - Amilia, Dinda; Kaus, Noor Haida Mohd; Hamid, Muhammadin (Trends in Sciences, 2026)
MnFe₂O₄/activated carbon composites have emerged as multifunctional materials that combine the catalytic and magnetic properties of manganese ferrite with the high surface area, porosity, and chemical stability of activated carbon. Structural characterizations confirm the successful formation of crystalline spinel MnFe₂O₄ phases uniformly dispersed within the carbon matrix, enhancing stability and reducing nanoparticle agglomeration. These composites exhibit outstanding adsorption and photocatalytic efficiencies, achieving high removal rates for pesticides, antibiotics, nutrients, and aromatic organics, while showing promise for microwave absorption, electrocatalysis, and energy conversion. Waste-derived activated carbon precursors, such as coconut shells, coffee husks, and durian peels, further improve sustainability and cost-effectiveness, aligning with circular economy principles. Mechanistic studies reveal synergistic pollutant removal: MnFe₂O₄ provides redox-active sites and magnetic recovery, while activated carbon offers functional groups, facilitates electron transfer, and mitigates charge recombination. Despite these advantages, challenges persist in scalability, long-term regeneration, and real-world applications in complex wastewater matrices. Future work should prioritize green, scalable synthesis, pilot-scale trials, and hybrid treatment systems to translate MnFe₂O₄/activated carbon composites into practical environmental and energy technologies. HIGHLIGHTS MnFe₂O₄/activated carbon composites integrate the magnetic and catalytic activity of ferrite with the high surface area and functionality of carbon materials Structural characterizations confirmed the formation of crystalline spinel MnFe₂O₄ uniformly dispersed within the activated carbon matrices. The composites exhibited high adsorption and photocatalytic performances Synergistic mechanisms enhance pollutant removal through redox active sites, improved electron transfer, and suppressed charge recombination. Challenges related to scalability, regeneration stability, and real wastewater applications highlight the directions for future research. GRAPHICAL ABSTRACT